Islamist Civil Society Activism Malaysia Abdullah: Angkatan Belia Islam Malaysia (ABIM) Darul Arqam - Hamid, Ahmad Fauzi Abdul (Studia Islamika, 2009)
Without discounting the relevance of such a framework, this article seeks to look at the phenomenon of Islamism in Malaysia from the angle of Islamist civil society movements that are not directly involved in the domain of electoral politics, but that have nonetheless significantly in fenced political behavior of especially the majority Malay-Muslim population of Malaysia. The provisional impact of these new groupings form the main thread in our discussion, which narrows down to an investigation into the metamorphoses that have a?ected and transpired in two of the most influential civil society movements in contemporary Islamism in Malaysia, viz. ABIM and Darul Arqam.DOI: 10.15408/sdi.v16i3.475